Acral pityriasis rosea: A rare variant of pityriasis rosea - Tantanasrigul, Pimpa; Wichaidit, Mingkwan; Kullavanijaya, Preya (Dermatology Reports, 2021)
Pityriasis rosea (PR) is a common, selflimited inflammatory skin condition, usually affects the trunk and proximal extremities. A variety of atypical manifestations of PR have been recognized ranging from the difference in the morphology, distribution, and course. Herein, the rare form of acral PR in an adult has been illustrated as the 29- year-old Thai female who presented with generalized erythematous papules and plaques with peripheral collarette scales on the trunk and extremities, prominently on the hands and feet.[...]